Možnosti využití vláken na bázi druhotných a snadnoobnovitelných surovin při výrobě pokročilých stavebních materiálů - Horáková, Lucie (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce se zabývala možnostmi využití vláken na bázi druhotných a snadnoobnovitelných surovin při výrobě pokročilých stavebních materiálů. Teoretická část obsahuje literární rešerši výzkumů, které se této problematice věnovaly. V rámci teoretické části byly vytipovány vhodné zdroje vláken a poznatky byly dále využity v praktické části diplomové práce. V rámci praktické části bylo provedeno laboratorní měření a následný výběr nejvhodnějších vláken. Poté byl proveden návrh receptur tepelně izolačních omítek (s možností využití i jako omítek sanačních) na bázi lehkého kameniva z pěnového skla, na který bylo navázáno výrobou zkušebních těles. Byly provedeny laboratorní zkoušky na čerstvých i zatvrdlých maltách, které byly následně vyhodnoceny. Závěrem bylo provedeno ekonomické vyhodnocení a zhodnocení konkurenceschopnosti navržených omítek.

The diploma thesis dealt with the possibilities of of utilization fiber-based and secondary easy-renewable raw sources in the production of lightweight building materials. The theoretical part includes literature search of the researches, which dealt with this issue. Appropriate sources of fibers were selected within the theoretical part and the findings were used in the practical part of the thesis. Within the practical part laboratory measurements and subsequent selection of the most suitable fibers were performed. Laboratory measurements and subsequent selection of the most suitable fibers were performed in the practical part. Subsequently, designs of thermal insulating plasters (with the possibility of using as repairing plasters) were made on the basis of lightweight glass aggregate, to which the production of test specimens was connected. Laboratory tests were performed on fresh and hardened mortars and subsequently evaluated. In conclusion, an economic evaluation and assessment of the competitiveness of the proposed plasters was carried out.
Possibilities of utilization fiber-based and secondary easy-renewable raw sources in the production of lightweight building materials
Keywords: Vlákna na bázi druhotných surovin; vlákna na bázi samoobnovitelných surovin; tepelně izolační omítka; sanační omítka; lehké kamenivo z pěnového skla; součinitel tepelné vodivosti.; Fibers based on by-products; fibres based on easy-renewable raw sources; thermal insulating plaster; repairing plaster; lightweight aggregate based on foam glass; thermal conductivity.